STUDI EFISIENSI PENDISTRIBUSIAN AIR IRIGASI SALURAN TERSIER PADA DAERAH IRIGASI DI DESA KARANG BAYAN KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - AGUSTINUS BEKE LALO; LALU HARDI WIJAYA; NI MADE NIA BUNGA SURYA DEWI; ARIANTO ARIANTO (SOSIAL SAINS DAN TEKNOLOGI, 2021)
The research design uses a descriptive quantitative approach, which explains the state of the efficiency of water distribution in Karang Bayan, Lingsar District, West Lombok Regency. The data used in the analysis are water flow velocity (VAV), cross-sectional area (A), channel flow rate (Q), water demand for plants and water requirements for each irrigation area, and the efficiency of irrigation water distribution in each channel (E). The results showed that the S3 and S4 channels did not meet the water needs in the irrigation area, while the discharge in the tertiary irrigation canals S1, S2, S5 and S6 was sufficient to meet the water needs of the irrigation area in Karang Bayan Village. Because the availability of water in the Mencongah Weir is very sufficient for providing water to the tertiary canal. Channel S1 which has an irrigation area of 36.64 ha and a channel length of 700 m with an actual discharge of 44.8 ltr/s has an irrigation efficiency of 60%. The S2 channel which has an irrigation area of 57,115 ha and a channel length of 900 m with an actual discharge of 67.9 ltr/s has an irrigation efficiency of 60%. In the S1 and S2 channels, the efficiency value is above 50-60%, then the channel can be said to be efficient